You tell us [IT advances].
This paper describes several IT-related projects that either succeeded or failed to achieve their respective design objectives. These projects include the Cisco/Yahoo's DKIM e-mail security system for eliminating spam, the Information Technology for European Advancement program, the Matshushita/Intel laptop PC that runs on a single battery charge for over eight hours, the fingerprint ID system for wireless keys from Privaris Inc., the broadband-over-power-line (BPL) project from IBM Corp. and CenterPoint Energy, Luxtera silicon photonics technology from Carisbad, and the special coprocessor from ClearSpeed Technology PLC.
Keywords: DKIM e-mail security system; Information Technology for European Advancement program; Broadband-over-power-line (BPL) project; Coprocessor; Fingerprint ID system for wireless keys; Silicon photonics